Identifikasi hasil tangkapan dan keuntungan nelayan tangkap di Kelurahan Kessilampe Kecamatan Kendari Kota Kendari - Saadia; Alam Lawelle, Sjamsu; Mansyur, Akhmad (Universitas Halu Oleo, 2021)
This research aims to determine the types of fish and the profit of handline fishing and traps in Kessilampe Sub Distric, Kendari District, Kendari City and conducted from August to September 2020. The sampling technique used the saturated sampling or census (21 respondents) namely 20 hand line fisherman and 1 trap fisherman. Collecting data through interviews, questionnaires, observation and documentation. The data analysis used was descriptive analysis and quantitative analysis. The results showed that hand line fisherman produce 263kg/year which was accumulated from 10 types of fish (coronation grouper, spotted coastal trevally,pinkear emperor, paddletail snapper, bigeye scad, indian mackerel, narrow-barred Spanish mackerel, mackerel scad, yellowback fusilier, horse-eye jack ): trap fisherman can produce 14kg/year consisting of 4 types of fish (foursaddle grouper, parrot fish, javan rabbitfish, whitespotted rabbitfish). The profit of handline fishing is IDR349,496/year, while the trap are only IDR 361,950/year. Handline fishing business more profitable than compared to bubu fisherman. In addition, fishing traps can be used as a side business for handline fisherman in Kessilampe Sub District, Kendari District, Kendari City.